Correlation of Sonographic Findings and Histopathological Examination of Hysterectomy Specimens in Perimenopausal Patients with Abnormal Uterine Bleeding - Muhammad Jamil Johar, Maria Riaz, Nasreen Akhtar, Sara Akram, Farzana Sabir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abnormal uterine bleeding (AUB) is a frequent prenatal problem that affects the women of all ages. AUB is the condition in which vaginal bleeding occur in the absence of pregnancy. The most common and easily available imaging procedure is the ultrasonography. Our study aimed to investigate the correlation between sonographic findings and histopathological examination of hysterectomy specimens in perimenopausal women with AUB. Study design: It is a cross-sectional study conducted at Lady Willingdon Hospital Lahore and Divisional Headquarters Teaching Hospital Mirpur, Azad Kashmir for the duration of six months from July 2022 to December 2022. Material and Methods: This study on hysteroscopy was carried out on 50 patients suffering from uterine bleeding and having a biopsy. All the patients selected in the given study were according to the inclusion criteria, while those patients were excluded that do not fulfill the inclusion criteria. Most of the patients included in this study had ages between 31 to 41 years. The study was approved by the review and ethical board committee of the hospital. Results: Most patients having this ultrasonography had fibroid and bulky uterus. Only a few had Adenomyosis and thick endometrium. Neglectable patients had an endometrial polyp and malignancy issues. The sensitivity value for the normal endometrium used as a control was at an acceptable range and it was used as the control for the further evaluation of other attributes. Conclusion: For the diagnosis of abnormal uterine bleeding, hysteroscopy is an excellent diagnostic tool and it is highly efficient for the estimation of pathological issues of the endometrium wall. Keywords: Abnormal uterine bleeding, sonography and histopathological examination.